2017
DOI: 10.3389/fpls.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification in Millets: A Sustainable Approach for Nutritional Security

Abstract: Nutritional insecurity is a major threat to the world’s population that is highly dependent on cereals-based diet, deficient in micronutrients. Next to cereals, millets are the primary sources of energy in the semi-arid tropics and drought-prone regions of Asia and Africa. Millets are nutritionally superior as their grains contain high amount of proteins, essential amino acids, minerals, and vitamins. Biofortification of staple crops is proved to be an economically feasible approach to combat micronutrient mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 143 publications
0
55
0
Order By: Relevance
“…In general, calcium transporters are involved in the cellular compartmentalization of calcium in different plant organs. Three major gene families of calcium transporter proteins have been described: (i) Ca 2+ -transporting P-type-ATPases [endoplasmic reticulum-type Ca 2+ -ATPase (ECA/IIA Type) and autoinhibited Ca 2+ -ATPase (ACA/IIB-type)], (ii) divalent cation–H + antiporters/exchangers [cation/H + antiporters (CAX), CCX and CHX], and (iii) Ca-permeable ion channels that include mechanosensitive calcium-permeable channels (MSCCs), glutamate receptors (GLRs), CNGCs and two-pore channels (TPC) ( Vinoth and Ravindhran, 2017 ). The highly significant SNP-markers ( Table 1 and Supplementary Table S3 ) could either be derived from the causative genes themselves or be in linkage to the causative genes for the identified QTLs for Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In general, calcium transporters are involved in the cellular compartmentalization of calcium in different plant organs. Three major gene families of calcium transporter proteins have been described: (i) Ca 2+ -transporting P-type-ATPases [endoplasmic reticulum-type Ca 2+ -ATPase (ECA/IIA Type) and autoinhibited Ca 2+ -ATPase (ACA/IIB-type)], (ii) divalent cation–H + antiporters/exchangers [cation/H + antiporters (CAX), CCX and CHX], and (iii) Ca-permeable ion channels that include mechanosensitive calcium-permeable channels (MSCCs), glutamate receptors (GLRs), CNGCs and two-pore channels (TPC) ( Vinoth and Ravindhran, 2017 ). The highly significant SNP-markers ( Table 1 and Supplementary Table S3 ) could either be derived from the causative genes themselves or be in linkage to the causative genes for the identified QTLs for Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Millet is one of the most important drought-resistant whole grain in arid and semiarid areas of Asia and Africa. It has attracted specific attention on account of the excellent nutritional value and potential health benefits such as anti-oxidant and anti-arteriosclerotic possibility [13,14]. Several studies have shown that millet, as a kind of functional food, is playing an unignoring role in maintaining homeostasis of blood glucose [15,16], delaying gastric emptying [17,18], and enhancing immune competence.…”
Section: Introductionmentioning
confidence: 99%
“…Pearl millet is a staple food for more than 90 million people in Africa and Asia, thus the nutritional quality of the grains has a big impact on the diet of these populations. Efforts to improve this crop are increasing (reviewed by [ 56 58 ]) and very recently the sequence of pearl millet genome was released [ 43 ], opening new opportunities for accelerating breeding of this species. With the purpose to contribute to the knowledge needed for breeding programs regarding nutritional traits of pearl millet, here we analysed the content of the major antinutrient phytic acid and of the goitrogenic C-glycosylflavones of the grain and provide information on genes involved in their biosynthesis.…”
Section: Discussionmentioning
confidence: 99%